Signal Processor for Millimetric Wave Radar Seeker for Antitank Guided Missile - Rao, N. Rama; Rao, K. Veerabhadra (Defence Science Journal, 2013)
The missile borne signal processor for the millimetric wave active radar seeker of the third generation type antitank guided missile (ATGM) system with lock-on-before-launch capability is discussed. The range and angle tracking systems are described and the results are presented. Feasible improvements in signal processor using coherent-on-receive scheme for achieving higher ranges, have been identified and are being implemented.